∫ 1 2 1 π / 6 6 1 π / 3 ( cos x + sin x ) d x
If the integral above can be expressed as 1 + b a , what is the value of a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i did the same way
We know that
cos
x
+
sin
x
is a periodic function with a period of
2
π
hence the above integral can be written as
=
∫
2
0
π
+
6
π
2
0
π
+
3
π
(
cos
x
+
sin
x
)
d
x
=
∫
6
π
3
π
(
cos
x
+
sin
x
)
d
x
After solving this we get
1
+
3
2
so
2
+
3
=
5
I solved this but what was that word you were talking about? @Abhishek
Was it (the "mere" word) 'Periodic' ?
Firstly note that in trigonometry 3 6 1 π ≡ 3 π a n d 6 1 2 1 π ≡ 6 π This yields ∫ 6 π 3 π ( c o s x + s i n x ) d x = [ c o s x − s i n x ] 6 1 π 3 1 π = ∣ c o s 3 1 π + s i n 3 1 π ∣ − ∣ c o s 6 1 π + s i n 6 1 π ∣ = ∣ 2 1 − 2 3 ∣ − ∣ 2 3 − 2 1 ∣ = 3 − 1 = 1 + 3 2 ∴ a + b = 5
Problem Loading...
Note Loading...
Set Loading...
∫ 6 1 2 1 π 3 6 1 π ( c o s ( x ) + s i n ( x ) ) d x ∫ 2 0 π + 6 π 2 0 π + 3 π ( c o s ( x ) + s i n ( x ) ) d x ∫ 6 π 3 π c o s ( x ) d x + ∫ 6 π 3 π s i n ( x ) d x I n t e g r a t i n g a n d r e a r r a n g i n g t h e t e r m s , s i n ( 3 π ) − s i n ( 6 π ) − c o s ( 3 π ) + c o s ( 6 π ) 2 3 − 2 1 − 2 1 + 2 3 3 − 1 N o w , w e n e e d t o b r i n g i t i n t e r m s o f 1 + b a M u l t i p l y i n g a n d d i v i d i n g 3 + 1 , ( 3 + 1 ) ( 3 − 1 ) ( 3 + 1 ) ( 1 + 3 ) 2 C o m p a r i n g , a = 2 , b = 3 . S o , a + b = 5
CHEERS!!:)